Evaluation of growth and nutrient uptake of rice genotypes under different levels of salinity - Shultana, Rakiba; Othman, Radziah; Tan, Ali Kee Zuan; Yusop, Mohd Rafii (Gaurav Society of Agricultural Research Information Centre, 2019)
Successful evaluation is necessary to ensure suitability of certain rice varieties in coastal saline areas. In this study, solution culture methods were employed to observe the salinity tolerance of seven rice genotypes under four salinity levels of 0, 4, 8 and 12 dS/m at seedling stages. The traits of shoot and root length, dry weight, ratio of Na+: K+ and Na+: Ca2+ and uptake of N, P and K were measured. The growth characters and chemical properties of rice seedlings revealed that only Pokkali was able to survive and could tolerate the NaCl toxicity up to 12 dS/m, while BRRI dhan67 and BINA dhan8 were tolerant at 8 dS/m and BRRI dhan47 and Putra-1 were moderately tolerant at 8 dS/m. Besides MR284 and MR297 can tolerant up to 4 dS/m. The findings can explore new ideas for future research particularly in selection of the suitable rice variety for targeted saline prone areas.